2010
DOI: 10.1038/mt.2010.146
|View full text |Cite
|
Sign up to set email alerts
|

A Short Pulse of IL-4 Delivered by DCs Electroporated With Modified mRNA Can Both Prevent and Treat Autoimmune Diabetes in NOD Mice

Abstract: Bone marrow-derived dendritic cells (DCs) are cells of the immune system that have been used as a tool to boost, modulate, or dampen immune responses. In the context of autoimmunity, DCs can be modified to express immunoregulatory products encoded by transgenes, and used therapeutically in adoptive cellular therapy. DCs that were lentivirally transduced (lt) to express interleukin 4 (IL-4) can significantly delay or prevent the onset of autoimmune diabetes in nonobese diabetic (NOD) mice. However, modifying ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 29 publications
1
55
0
Order By: Relevance
“…Thus, the use of receptor-selective superkines in mouse models will help to both better delineate the mode of action of therapies involving IL-4 and improve their efficacy 29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the use of receptor-selective superkines in mouse models will help to both better delineate the mode of action of therapies involving IL-4 and improve their efficacy 29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…These cells are H2-K d+ and I-A g7− fibroblastic reticular cells. DCs were generated in vitro from the bone marrow of NOD mice depleted of T cells, B cells, and granulocytes after 6–7 days of culture in the presence of GM-CSF and IL-4 (Peprotech, 10 ng/mL) 52 . DAPg7 and PCRC-5 cells were transduced with the different LV particles, sorted based on similar GFP levels between transduced lines.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, other studies have shown that disease remission can be established when administering unloaded tolDCs . This may suggest that tolDCs are able to take up the relevant antigen in vivo .…”
Section: The Problem Of Targeting Autoantigen(s) – Which Ones?mentioning
confidence: 80%
“…27,42,43 More recent research shows that this is also applicable in other autoimmune diseases. 44 Furthermore, when comparing the therapeutic action of unloaded tolDCs and tolDCs loaded with a disease relevant peptide (MOG [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] in the experimental autoimmune encephalomyelitis model, Mansilla et al 45 showed that although the unloaded tolDCs inhibited disease symptoms, the MOG 40-55 -loaded tolDCs diminished disease even more.…”
Section: Tolerogenic Dendritic Cells As a Therapeutic Toolmentioning
confidence: 99%
See 1 more Smart Citation